INTERNALISASAI NILAI-NILAI AKHLAK SUFI MELALUI PENGKAJIAN KITAB SIRRUL ASRAR PADA IKHWAN THARIQAH QADIRIYYAHNAQSYABANDIYYAH DI PESANTREN SURYALAYA TASIKMALAYA - Hidayat, Dudung Rahmat (2012)
The research was motivated by the reality of people's lives and our nation today. Where there are varieties of strange behaviors -even crisis of moral and character has happened and is happening. Muslims, who are 23% of the 5.6 billion inhabitants of the earth, is less prominent, left, and less practicing Islamic values. Muslim internal conflicts often occur, for example, disputes, quarrels, clashes, power struggles, and easily played off. Such phenomena have also occurred in the time of Shaikh 'Abd Al-Qadir Al-Jailani (SAQJ). He managed to find a solution how to solve them, by introducing some ideas, ways, and strategies. Some of them are contained in the book Sirr al-Asrâr fîmâ Yahtâju ilaihi al-Abrâr. This study is (1) to describe the structure of the presentation of the theme in Sirr al-Asrâr, (2) to explain the moral values contained in the book of Sufi of Sirr al-Asrâr, and (3) to describe the methods of cultivation of Sufi moral values of the Sirr al-Asrâr. The study used descriptive qualitative analytic method. The stages are the data preparation process that includes categorization and recording, data reduction, data withdrawal, and discussion. Data collections cover with content analysis techniques, interviews, and observation. The results show that to address community issues such as conflict, disputes, quarrels, feud, corruption, etc., then the solution must come from the will and self-awareness. Knowing ourselves as creatures of God will open the way to get to know Al-Khaliq, Allah ta'âla, which in turn will push to increase the zikr to Him; cleansing body and soul from the dirt, stains and sins through riyadah taqarrub to Him. Book of Siirr contains therapy, and an explanation of how a person should do when he wants to achieve the perfect degree of knowledge and taqwa to Allah ta'âla. The process of internalization of Sufi values is done through various ways and certain stages, namely: a) talqîn, for anyone who is just learning zikr, receiving talqîn by murshid or by representative of talqîn, b) tanbîh, a memorial and pledge to implement the rules of murshid that must be obeyed by all brothers, c) daily zikr, d) khataman, and e) manaqiban and the other relevant events. The study recommends 1) the General Education Program to stabilize the gait and the existence of its graduates in the community, by developing methods, strategies and messages of thinkers and practitioners of Sirr al-Asrâr, accompanied by innovations from thinkers and practitioners that came later; 2) the lecturers, teachers, and other mainly engaged in the field of guidance of moral, faith, and piety to be consistent to think of a solution to the problems of Muslims in particular and the problems of the nation in general, by maintaining the good old values and taking the better new values.